Does Urinary Catheterization Affect the Quality of Death in Patients with Advanced Cancer? A Secondary Analysis of a Multicenter Prospective Cohort Study - Higashibata, Takahiro; Hamano, Jun; Hisanaga, Takayuki; Hagiwara, Shingo; Shimokawa, Miho; Yabuki, Ritsuko; Yokomichi, Naosuke; Shimoinaba, Junichi; Kamura, Rena; Baba, Mika; Funaki, Hiromi; Mori, Masanori; et al. (Journal of palliative medicine, 2022)
Patients with life-limiting illnesses frequently experience urinary difficulties, and urinary catheterization is one of the interventions for managing them. However, evidence supporting the effects of urinary catheters on the quality of death (QoD) is lacking in this population. To investigate whether urinary catheterization affects QoD in patients with advanced cancer in palliative care units. A secondary analysis of a multicenter, prospective cohort study. The study enrolled consecutive patients with advanced cancer admitted to palliative care units in Japan between January and December 2017. Those who were not catheterized on admission and who died while in a palliative care unit were analyzed. QoD was evaluated at death using the Good Death Scale (GDS). Of 885 patients, 297 (33.6%) were catheterized during their palliative care unit stay. Females and patients with a long palliative care unit stay were more likely to be catheterized. In inverse probability-weighted propensity score analysis, patients with urinary catheterization during their palliative care unit stay had higher total GDS scores than those without catheterization (coefficient 0.410, 95% confidence interval 0.068-0.752). In subgroup analyses stratified by sex, age, and length of palliative care unit stay, urinary catheterization was associated with higher total GDS scores in patients younger than 65 years of age and those who died after a palliative care unit stay of 21 days or fewer. This study suggested that urinary catheterization during a palliative care unit stay may have a positive impact on overall QoD in patients with advanced cancer. This study was registered in the UMIN Clinical Trials Registry (UMIN000025457).